BosR Functions as a Repressor of the ospAB Operon in Borrelia burgdorferi - Shi, Yanlin (Public Library of Science, 2014)

(untitled)
The Lyme disease spirochete, Borrelia burgdorferi, must abundantly produce outer surface lipoprotein A (OspA) in the tick vector but downregulate OspA in mammals in order to evade the immune system and maintain its natural enzootic cycle. Here, we show that BosR binds two regulatory elements of the ospAB operon and that increasing BosR expression leads to downregulation of OspA. Both regulatory sequences, cisI and cisII, showed strong BosR-binding and cisII bound much tighter than cisI. A promoterless bosR gene fused with an inducible promoter was introduced into an rpoS mutant and a wild-type strain to assess RpoS-independent and -dependent downregulation of OspA by BosR. With the induction of BosR expression, OspA expression was reduced more significantly in the RpoS-deficient than wild-type background, but not completely repressed. In the presence of constitutive expression of OspC, DbpA and DbpB, increasing BosR production resulted in complete repression of OspA in the RpoS mutant. Taken together, the study clearly demonstrated BosR serves as a repressor that binds both regulatory elements of the ospAB operon and shuts off expression.